2019
DOI: 10.3889/oamjms.2019.080
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Skeletal Effects of Rapid Maxillary Expansion in Pre and Post Pubertal Subjects: A Systematic Review

Abstract: OBJECTIVE: The aim of this systematic review was to assess the transverse skeletal effects of rapid maxillary expansion (RME) in pre and post-pubertal subjects. MATERIAL AND METHODS: Five databases were searched till May 2018; Pubmed, Cochrane, Scopus, Lilacs and Web of science in addition to the manual search of other sources. There were no language restrictions. Methodological Index for Non-Randomized Studies MINORS was used to assess the quality and risk of bias of the trials included. RESULTS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 93 publications
0
12
0
3
Order By: Relevance
“… 56 A systematic review published in 2019 included a descriptive analysis of six studies; the results suggested that rapid arch expansion achieved maxillary and nasal lateral wall widening by 3.4 mm and 3.3 mm, respectively; these distances decreased to 2.8 mm and 2.2 mm after puberty. 57 For arch expansion performed before puberty, the width of the upper alveolar seat and maxilla increased continuously and steadily during long-term follow-up; for the arch expansion performed after puberty, only the nasal lateral wall increased by 1.3 mm, compared with the control group, while the maxillary bony width did not increase. A 2016 Cochrane systematic review (quasi-RCT, n = 23 patients; AMSTAR 2 = 15) compared personalized oral appliances with non-intervention treatment in children with OSA (AHI > 1).…”
Section: Clinical Questionsmentioning
confidence: 79%
“… 56 A systematic review published in 2019 included a descriptive analysis of six studies; the results suggested that rapid arch expansion achieved maxillary and nasal lateral wall widening by 3.4 mm and 3.3 mm, respectively; these distances decreased to 2.8 mm and 2.2 mm after puberty. 57 For arch expansion performed before puberty, the width of the upper alveolar seat and maxilla increased continuously and steadily during long-term follow-up; for the arch expansion performed after puberty, only the nasal lateral wall increased by 1.3 mm, compared with the control group, while the maxillary bony width did not increase. A 2016 Cochrane systematic review (quasi-RCT, n = 23 patients; AMSTAR 2 = 15) compared personalized oral appliances with non-intervention treatment in children with OSA (AHI > 1).…”
Section: Clinical Questionsmentioning
confidence: 79%
“…The clinical goal of RME is to widen the maxilla transversally, without disturbing the integrity of the midpalatal suture. [28][29][30] A significant decrease in BMD will weaken the suture and will require additional post-expansion (retention) time to allow the suture to recover its original bone density levels. Therefore, higher bone mass in the midpalatal suture is likely to have beneficial effects in reducing the retention period and preventing relapse following expansion.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical goal of RME is to widen the maxilla transversally, without disturbing the integrity of the midpalatal suture 28‐30 . A significant decrease in BMD will weaken the suture and will require additional post‐expansion (retention) time to allow the suture to recover its original bone density levels.…”
Section: Discussionmentioning
confidence: 99%
“… 38 Regarding the optimal age for orthodontic treatment, a systematic review established that rapid arch expansion was significantly more effective before puberty. 39 Another systematic review found that a mandibular advancement device reduced AHI in both younger (6–9.5 years) and older children (9.5–13 years), suggesting that these devices can be used to treat OSA before the age of 13 years. However, no data are available for older adolescents.…”
Section: Non-surgical Treatment Of Pediatric Osamentioning
confidence: 99%